Identification of Ectoparasites on Aglaonema sp. in Ngerong Village, Pasuruan City with Visual Encounter Methods - Ilmiyah, Silvi Zakiyatul; Setiyanto, Afif Eka Rahma; Ibrahim, Yudhistira; Yanuwiadi, Bagyo; Gama, Zulfaidah Penata (Universitas Andalas, 2024)
Ornamental plants are plants that are used as decoration. One of the ornamental plants is Aglaonema sp. known as Sri Rejeki. It is enjoyed as an ornamental plant in terms of leaf pattern. However, Aglaonema has harmful ectoparasites. The aim of this study was to determine and identify ectoparasites in Aglaonema plants using the Visual Encounter method, and to analyze the role and solutions for the presence of ectoparasites in Aglaonema. Research observations were carried out for approximately three weeks from April to May 2022. Six individuals Aglaonema were used as samples. Observation was done by using the visual encounter method which was carried out once a week in the morning, afternoon, and evening with a total of three time observations (15 minutes each) at each time. Measurement of abiotic factors includes temperature, humidity, and weather. The results were used to determine the important value index (IVI) and Shannon-Wiener Index (H’). All identified organisms were arthropods (insects). There were five identified families: Pseudococcidae, Coccidae, Formicidae, Chironomidae, and Muscidae. Pseudococcidae and Coccidae were the insect families that are confirmed as ectoparasites for plants. The solution for prevention or termination of ectoparasite is by replacing the invaded plant away from healthy plants, removing the infected parts of plant, and/or placing refugia plant for habitat of ectoparasite’s natural enemies.